2003
DOI: 10.1247/csf.28.431
|View full text |Cite
|
Sign up to set email alerts
|

The Structure and Function of GGAs, the Traffic Controllers at the TGN Sorting Crossroads

Abstract: ABSTRACT. GGAs (Golgi-localizing, g-adaptin ear homology domain, ARF-binding proteins) are a family of monomeric clathrin adaptor proteins that are conserved from yeasts to humans. Data published during the past four years have provided detailed pictures of the localization, domain organization and structure-function relationships of GGAs. GGAs possess four conserved functional domains, each of which interacts with cargo proteins including mannose 6-phosphate receptors, the small GTPase ARF, clathrin, or acces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 89 publications
(143 reference statements)
0
37
0
1
Order By: Relevance
“…Like Tom1 and GGAs, Tom1L1 interacts with ubiquitin through the GAT domain (Bonifacino, 2004;Katoh et al, 2004;Nakayama and Wakatsuki, 2003;Shiba et al, 2004;Yamakami et al, 2003) and, like Tom1, with clathrin through the C-terminal region (Colilin et al, 2007;Katoh et al, 2006;Katoh et al, 2004;Yamakami et al, 2003). In the MVB pathway, ubiquitin functions as a sorting signal for degradation; ubiquitinated cargo proteins, such as the EGF receptor, are recognized by Hrs and sorted into the MVB by sequentially interacting with ESCRT complexes, including Tsg101-containing ESCRT-I (Piper and Katzmann, 2007;Slagsvold et al, 2006;Williams and Urbé, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like Tom1 and GGAs, Tom1L1 interacts with ubiquitin through the GAT domain (Bonifacino, 2004;Katoh et al, 2004;Nakayama and Wakatsuki, 2003;Shiba et al, 2004;Yamakami et al, 2003) and, like Tom1, with clathrin through the C-terminal region (Colilin et al, 2007;Katoh et al, 2006;Katoh et al, 2004;Yamakami et al, 2003). In the MVB pathway, ubiquitin functions as a sorting signal for degradation; ubiquitinated cargo proteins, such as the EGF receptor, are recognized by Hrs and sorted into the MVB by sequentially interacting with ESCRT complexes, including Tsg101-containing ESCRT-I (Piper and Katzmann, 2007;Slagsvold et al, 2006;Williams and Urbé, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The GAT domain of both the GGA (Golgi-localizing, γ-adaptin ear domain homology, Arf-binding protein) and Tom1 family proteins was shown to bind ubiquitin (Bonifacino, 2004;Nakayama and Wakatsuki, 2003), suggesting their implication in sorting of ubiquitinated proteins to the MVB pathway (Katoh et al, 2006;Katoh et al, 2004;Puertollano and Bonifacino, 2004;Scott et al, 2004;Shiba et al, 2004;Yamakami et al, 2003); for review, see Hurley et al, 2006;Nakayama and Wakatsuki, 2003;Piper and Luzio, 2007. Recently, Puertollano reported that, by using a yeast two-hybrid system, Tom1L1 is able to interact with Tsg101 through a PTAP sequence located near the N-terminus of the GAT domain (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Adaptor protein complexes (AP) are required to recruit cargo into coated vesicles thus playing an essential role in cargo selectivity of the transport vesicle in traffic between the trans-Golgi network (TGN) and endosomes (Owen et al, 2004). Gga proteins are monomeric clathrin adaptor proteins mediating TGN to the endosome transport (Nakayama and Wakatsuki, 2003). Apart from the AP complexes and the monomeric GGA adaptors, the list is expanding to new sets of adaptors, which are specific to only a particular type of cargo or to one family of cargo (Bonifacino and Rojas, 2006).…”
mentioning
confidence: 99%
“…They consist of four distinct domains: a VHS domain that binds the acidic dileucine sorting signal (DXXLL) found in the MPRs and other transmembrane cargo proteins; the GAT domain, which interacts with the GTP-bound form of ARF1; a hinge region, which recruits clathrin; and a GAE domain, which exhibits sequence similarity to the ear region of ␥ adaptin and recruits a number of accessory proteins (Ref. 13 and references therein). The interaction with the GGAs leads to the selective incorporation of the MPRs into clathrin-coated vesicles destined for the endosomal/lysosomal sorting route.…”
mentioning
confidence: 99%